WASTE BANK AS AN ALTERNATIVE TO COMMUNITY-BASED WASTE MANAGEMENT - Elly Kristiani Purwendah; Daniel Joko Wahyono (Jurnal Komunikasi Hukum, 2022)
This study aims to (1) find out and analyze how the waste bank program is managed, and (2) find out and analyze how the benefits of the waste bank program are as an effort to empower the community. The type of research used is normative legal research. The data obtained from this study were secondary data obtained through a literature study, then the data obtained were analyzed qualitatively juridically through a statutory and conceptual approach. The results of this study indicate that (1) the Waste Bank in its implementation can reduce the high number of waste in the community and in the final disposal site (TPA). Thus, through the Waste Bank, it is an alternative solution for the government and the community in reducing the increasing volume of waste. (2) Community-based waste management as an approach to waste management based on the active participation of the community. Environmental management requires the facilitation and implementation of community-based efforts as a strategy for empowering and increasing their access to environmental resources. The benefit of the Waste Bank for the community is that it can increase people's income because when they exchange their waste they will get a reward in the form of money collected in the account they have.